2022
DOI: 10.3390/healthcare10061055
|View full text |Cite
|
Sign up to set email alerts
|

Association between Obesity and Anemia in a Nationally Representative Sample of South Korean Adolescents: A Cross-Sectional Study

Abstract: Anemia is associated with physical, cognitive, and developmental problems. Given that there are limited studies on anemia prevalence among obese Asian adolescents and that past evidence is controversial, this study investigated the relationship between obesity and anemia in a nationally representative sample of South Korean adolescents. Data were obtained from the 2007–2019 Korea National Health and Nutrition Examination Survey. Overall, 10,231 subjects were included in the analysis. Multiple logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This trend for anemia in obesity was also observed in 251 female university students from Dubai, in which those with anemia also presented a higher mean of total body fat percentage (38.9%) [25]. Meanwhile, Jeong et al did not find an association between obesity and anemia in adolescents aged 10.21 years adjusting for sex, age, household income, and menarche, although in a subgroup analysis they found a positive association in the group of 10 to 13 years old [26]. Cepeda‐Lopez et al did not find a significant relationship between BMI as continuous variable or BMI cut‐points for obesity with hemoglobin levels, values of transferrin saturation or total iron binding capacity in women of reproductive age and children (5–12 years old) from the 1999 Mexican nutrition survey, in unadjusted and adjusted (age, area [rural/Urban], geographic region, parity, and iron intake) regression models [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend for anemia in obesity was also observed in 251 female university students from Dubai, in which those with anemia also presented a higher mean of total body fat percentage (38.9%) [25]. Meanwhile, Jeong et al did not find an association between obesity and anemia in adolescents aged 10.21 years adjusting for sex, age, household income, and menarche, although in a subgroup analysis they found a positive association in the group of 10 to 13 years old [26]. Cepeda‐Lopez et al did not find a significant relationship between BMI as continuous variable or BMI cut‐points for obesity with hemoglobin levels, values of transferrin saturation or total iron binding capacity in women of reproductive age and children (5–12 years old) from the 1999 Mexican nutrition survey, in unadjusted and adjusted (age, area [rural/Urban], geographic region, parity, and iron intake) regression models [27].…”
Section: Discussionmentioning
confidence: 99%
“…Findings on adiposity and ID or anemia in selected studies CRP, C reactive protein; EPP, erythrocyte protoporphyrin; Hb, hemoglobin; ID, iron deficiency; IOTF, International Obesity Task Force; MCV, mean corpuscular volume; OR, odds ratio; SF, serum ferritin; TIBC, total iron binding capacity; TSAT or TS, transferrin saturation; WC, waist circumference; WHR, waist-hip ratio; W-HtR, waist-to-height ratio.anemia in obesity was also observed in 251 female university students from Dubai, in which those with anemia also presented a higher mean of total body fat percentage (38.9%)[25]. Meanwhile, Jeong et al did not find an association between obesity and anemia in adolescents aged 10.21 years adjusting for sex, age, household income, and menarche, although in a subgroup analysis they found a positive association in the group of 10 to 13 years old[26]. Cepeda-Lopez et al did…”
mentioning
confidence: 94%
“…Several other studies have also found a relationship between plasma protein and obesity, albeit the results have been mixed [12][13][14]. A study in South Korean teens found an inverse relationship between teenage ferritin levels in serum and obesity; therefore, the relationship between serum proteins and obesity remains unknown [15]. Anemia has been linked to lower BMI and plasma protein levels, and research has shown that it is more common among college students from developing countries [16].…”
Section: Introductionmentioning
confidence: 99%